Systematics of Thiodinini (Araneae: Salticidae: Salticinae), with description of a new genus and twelve new species - Bustamante, Abel A.; Ruiz, Gustavo R.s. (Zootaxa, 2017)
The jumping spider tribe Thiodinini is revised at generic level: diagnoses are proposed for all valid genera, based on the type species of each genus, and in some cases, on new species herein described. The tribe contains seven genera: Thiodina Simon, 1900; Cyllodania Simon, 1902; Hyetussa Simon, 1902; Atomosphyrus Simon, 1902; Arachnomura Mello-Leitão, 1917, Titanattus Peckham & Peckham, 1885 and the new genus Tartamura gen. nov. The following genera are synonymized: Micalula Strand, 1932 and Bredana Gertsch, 1936 with Hyetussa Simon, 1902; Agelista Simon, 1900 with Titanattus Peckham & Peckham, 1885. With this, the following new combinations are established: Hyetussa longithorax (Petrunkevitch, 1925) comb. nov. (this species with a neotype designation), from Micalula, and Hyetussa complicata (Gertsch, 1936) comb. nov. and Hyetussa alternata (Gertsch, 1936) comb. nov., both from Bredana. A transfer is proposed: Thiodina minuta comb. nov. (from Cyllodania). Twelve new species are described: Arachnomura querandi sp. nov.; Cyllodania trinidad sp. nov.; Cyllodania zoobotanica sp. nov.; Hyetussa sergipe sp. nov.; Hyetussa tremembe sp. nov.; Tartamura agatelin sp. nov.; Tartamura huao sp. nov.; Tartamura metzneri sp. nov.; Thiodina firme sp. nov.; Thiodina perian sp. nov.; Titanattus acanjuba sp. nov. and Titanattus euryphaessa sp. nov. Morphological traits and aspects of the phylogeny are discussed.